Poly(Hydroxyamide) as Support for Thin-Film Composite Membranes for Water Treatment - Sanchez-Poblete, J (Springer Verlag, 2019)
Preparation of a porous support for a thin-film composite (TFC) membrane was achieved based on a highly aromatic poly(hydroxyamide) (PHA) formed from 5-hydroxyisophthalic acid and 4,4′-(hexafluoroisopropylidene)dianiline. PHA synthesis was confirmed by Fourier transform infrared and proton nuclear magnetic resonance (1H NMR) spectroscopies. PHA was soluble in N-methyl-2-pyrrolidinone (NMP), N,N-dimethylacetamide (DMAc), and tetrahydrofuran (THF) with Mw 6.1 × 104 Da. Moreover, PHA showed good thermal stability up to 390 °C. Parameters for an appropriated PHA porous structure support membrane by the phase-inversion method were determined. Porous PHA support offers higher thermal stability and better adhesion between support amide thin skin layer than the ones used actually. Water permeation flux was 543 L m−2 h−1 for PHA porous support, whereas thin-film composite membrane PHA-TFC formed presented a decrease in water permeation flux (2.5 L m−2 h−1) and a salt rejection capacity of 29% which situates it as a nanofiltration membrane. © 2018, Springer-Verlag GmbH Germany, part of Springer Nature.